Role of molecular descriptors in quantitative structure?property relationship analysis of kidney cancer therapeutics - Mahboob, Abid; Rasheed, Muhammad Waheed; Hanif, Iqra; Amin, Laiba; Alameri, Abdu (Wiley, 2024)
A topological index is a numerical parameter that describes the topology of the network. Topological indices are utilized in quantitative structure?activity relationship (QSAR) research to theoretically estimate the physicochemical characteristics of chemical compounds. In this article, we examine ten degree?based topological indices for kidney cancer drugs to aid researchers in understanding the physical properties and chemical bonding between them. We also defined two new numerical descriptors named "first terminal Zagreb index" and "second terminal Zagreb index" for the analysis and examination of seven properties of drugs. The boiling point, enthalpy of vaporization, molar volume, flash point, molar refraction, density, polar surface area, and molar weight of kidney medicine are analyzed using several degree?related topological indices. The linear and quadratic regression models are used to check the predictive power of TIs. The correlation coefficient is used to represent the results by determining the relationship between the estimated and experimental values of kidney cancer drugs. The numerical descriptors are suitable if the values of the correlation coefficients are greater than .7, the F?statistical values are higher than 2.5, and the p?values are less than .05. The results in this article fulfill the criteria for being significant. This theoretical approach may allow chemists and other professionals in the healthcare industry to forecast the properties of kidney cancer drugs without doing any tests.